ON THE RELATIONS BETWEEN THE UZBEK AND TAJIK LANGUAGES IN THE NATIONAL-CULTURAL SPACE OF THE REPUBLIC OF UZBEKISTAN (Eureka Journal of Language, Culture & Social Change, 2026)
The article analyzes interlingual contacts in the national and cultural space of Uzbekistan, with particular attention to the organic relations between the Uzbek and Tajik languages. The linguistic dimensions of the country’s multiethnic environment are examined, and the centuries-long interaction between Uzbek and Persian-Tajik is elucidated on a scientific basis at the phonetic, morphological, lexical, and syntactic levels. The study specifically highlights the weakening of vowel harmony (synharmonism) in Uzbek, the penetration of numerous Arabic and Persian-Tajik borrowings into the lexical stock and grammatical system, and the influence of Persian traditions on syntactic structures. In addition, the phenomena of bilingualism and code-switching are discussed, particularly through examples from the linguistic environments of Samarkand, Bukhara, Fergana, and Surkhandarya. The author reveals the linguistic and cultural significance of the interaction between Uzbek and Tajik and provides a scholarly analysis of its impact on language development and the cultural heritage of the peoples concerned.
Keywords: Uzbek language, Tajik language, interlingual contact, bilingualism, code-switching, borrowing, vowel harmony, lexical influence, morphological influence, syntactic influence, national and cultural space.